Islamic Education As An Effort To Strengthen Morals In The Era Of Globalization - Muhammad, Giantomi; Surana, Dedih; Sanusi, Iwan; Suhartini, Andewi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Islamic education at this time is very much needed to develop knowledge based on faith and piety. This results in a pattern of physical and spiritual behavior that produces a form of self-concept, namely, being a person with character. The weakening of moral attitudes in the personality of a Muslim is not a small problem and needs to be taken seriously. Islamic education has an impact on increasing faith and piety to form a person who has character, especially with the increase in the current era of globalization, which changes all aspects of life, including mindset. The purpose of this study is to find out the process of Islamic education as the actualization of Islamic teachings so that it can be an effort to strengthen the morals that occur in this era of globalization in the personality of Muslims. This research is qualitative research with the type of library research (Library Research). The results of this study show that the strengthening of morals by Islamic education in the current era of globalization in addressing present moral and ethical deviations includes the need for revitalization as moral strengthening that needs to be carried out by Muslims today in facing the era of globalization, including 1) applying a holistic learning model and based on morality, 2) revitalizing moral education, 3) revitalizing social education, and 4) revitalizing the role of technology. Keywords: Islamic Education, Morals, Globalization Era, Morals, Ethics.